Gamification in Mathematics Education: A Bibliometric Review of Post-Pandemic Research - Divia Utami Putri, Seandyta; Maulidya, Della; Lestary, Ratnah; Maryati, Ira; Marlina, Ekawati (JRPM (Jurnal Review Pembelajaran Matematika), 2025)
Gamification in mathematics education has risen post-COVID-19 to improve student engagement and learning. This study explores key trends, influential authors, and leading journals through bibliometric and keyword co-occurrence network analysis of 272 publications (2022–2024) from the ERIC database, using the Boolean search “(gamification OR games) AND (mathematics OR algebra OR geometry OR calculus OR statistics)”. Using Biblioshiny for Bibliometrix, the analysis identified 812 authors and 138 journals, with prominent contributors including Erin, Fengfeng, and Ji-Eun Lee. Leading journals, such as Education and Information Technologies and Journal of Computer Assisted Learning, emerged as key sources. Three main keyword clusters were identified: game-based learning in mathematics, development of early mathematical skills, and global educational perspectives. The study highlights trends such as problem-solving and student engagement, while revealing a limited research base on the cognitive and social impacts of gamification, particularly at the secondary level. It concludes with recommendations for future research to address gaps and support broader adoption.